ПРИСТАНАК НА ТЕТОВИРАЊЕ - Srdjan, (COLLECTION OF PAPERS, FACULTY OF LAW NIŠ, 2024)
With more than five-thousand-year long tradition, tattooing is considered to be one of the oldest art forms. And with the gradual development of new techniques, materials, styles and approaches to solve even most difficult technical problems, tattooing became highly appreciated way of self-expression for both tattoo artists and proud owners of tattoos.However, there is a number of legal issues associated with tattooing process. Copyright restrictions, health and safety concerns, licensing, even discrimination issues, to name just a few, attracted special attention of legislators and legal experts. But central question from legal standpoint, or cluster of questions to be precise, revolves around the consent to receive tattoo.Numerous questions related to personal autonomy arise in the moment when autonomy is expressed through consent, and legal capacity for self-expression certainly is the most important one. Since there is no adequate, or at least firm legal frame around tattooing practice in the Republic of Serbia, in this article, relying on different techniques of analytical and normative method, we present dilemmas and possible answers on different aspects of legal capacity to express personal autonomy by consenting to receive tattoo.
Keywords: tattooing; consent; contract; legal capacity; personal autonomy